Antecedents Of Lecturer Performance And Its Impact On Graduates' Competencies At Medan City University - Kuras Purba (Digital Innovation : International Journal of Management, 2025)
Education is an ongoing issue that continues to be researched over time. Private universities established by foundations are required to make efforts to enhance the competencies of their graduates, which results in high competitiveness. This study aims to examine the antecedents of lecturer performance and its impact on graduate competence at Medan city. The factors studied in the antecedents include: foundation management, university governance, and dean leadership and their effects on graduate competence. The population in this research is final semester students of the Management Study Program, Faculty of Economics, at nine private universities in Medan City. The sample selection in this study was carried out using multi-stage sampling, starting with purposive sampling of private universities and incidental sampling of students. The total sample in this study comprises 576 students representing the nine private universities proportionally. Data analysis used descriptive statistics and Structural Equation Modeling (SEM). This research concludes: (1) Foundation management has a positive and significant effect on university governance. (2) Foundation management has a direct positive and significant effect on dean leadership. (3) University governance has a positive and significant effect on lecturer performance. (4) University management has a positive and significant effect on dean leadership. (5) University governance has a positive and significant effect on lecturer performance. (6) Dean leadership has a positive and significant effect on lecturer performance. (7) Lecturer performance has a positive and significant effect on graduate competence. (8) Foundation management has a positive and significant effect on dean leadership through university governance.